STRATEGIC APPROACHES FOR MITIGATING CRISIS IN VILLAGE TOURIST DESTINATION SECTOR IN WEST KALIMANTAN - Nila Krisnawati (Fakultas Pariwisata Universitas Pancasila, 2021)
COVID-19 is the world crisis caused by Coronavirus, which a major fall down for the tourism industry. This study is done to analyze the strategic approach in mitigating tourist destinations and to prepare the destination for the recovery after the Coronavirus pandemic. The purpose of this research is to identify and analyze strategic approaches used for mitigation in the case study of Bagak Sahwa Village Tourism in Singkawang, West Kalimantan Province. The data used qualitative research method through 8 in-depth interviews and 1 focus group discussion as the source persons. In a cause of travel restriction, the qualitative data collection method was conducted virtually. This finding uses the village tourism approaches to analyze the strategy. Based on the findings, the community of Bagak Sahwa understanding of mitigation has increased and developed several strategies in mitigating their destination. The community expects the strategy for the improvement and development of the village destination from the local tourism office. Keywords:Tourist Crisis Management, Destination Mitigation, Strategic Management, COVID-19, Village Tourism